Identfying effective elements in the landscape of historical districts (Typical sample: Oudlaajaan neighborhood-Tehran) - Ensieh, Ghavampour; Zienab, Rabiee; Hossein, Norouzi; Seyyed Amir, Mansoori (2008)

(untitled)
The historical context of a city is part of its cultural property, reflecting its identity and visual values through forming the inhabitants’ collective memory and showing the lifestyle of their ancestors. One of the most important questions has always been: what are the factors that guarantee the permanence of the landscape of a historical context? Finding these factors and classifying them into a hierarchy, depending on their amount of effectiveness, will clarify how much change needs to be applied to each one of them; it will also make way for urban management authorities to start planning the changes. For this purpose, ‘Oudlaajaan - one of Tehran’s residential neighborhoods built in Safavid Dynasty - was chosen. This district has been registered by Tehran’s Cultural Heritage Organization for its historical value. But unfortunately, due to the wrong policies applied by the urban management during different eras, it has lost all its physical values. Our interpretation of a city’s landscape is in the first place visual, and is formed by moving inside the structure of the city and an association of ideas. There, we can experience the environment in the form of a series of visual intakes. The mind, then, establishes a connection between the past experiences and the new environment. On this basis, we divided the district into several survey blocks and chose some people of each block randomly to fill out our questionnaires, asking them about their visual experience of the district. Based on the results of both theoretical studies and the surveys, we could identify the dimension and shape of the pathways, signs and turning points, activities, architectural characteristics of the buildings and vegetation, serving as the most important landmarks of the district, a comprehensive understanding of which can lead to an explicit plan for applying changes to the context.